ECONOMIC ANALYSIS OF RED GRAM CULTIVATION IN GULBARGA DISTRICT OF KARNATAKA STATE - A. MEENA, RENUKA, R. VIJAYAKUMARI, MD. ALI BABA and (The Journal of Research, PJTSAU, 2019)
Red gram, a major pulse crop commonly known as Tur or Arhar in India is the second important pulse in the country after gram (chana). The ability of red gram to produce high economic yields under soil moisture deficit makes it an important crop in rain fed and dry land agriculture.